Van der Waals electride: Toward intrinsic two-dimensional ferromagnetism of spin-polarized anionic electrons. (September 2021) - Song, Hyun Yong; Yoo, Byung Il; Choi, Jin-Ho; Kang, Se-Hwang; Bang, Joonho; Li, Wei; Nandadasa, Chandani N.; Thapa, Dinesh; Yoon, Duhee; Han, Myung Joon; Lee, Kyu Hyoung; Kim, Seong Gon; et al.
Abstract: Discoveries of two-dimensional (2D) magnetism originated from confined atomic layers in van der Waals (vdW) crystals provide an interesting arena for elucidating its fundamentals and enrich magneto-electric and quantum properties. However, a material that exhibits intrinsic 2D magnetism of interstitial electrons occupying layered space, as a root system of magnetic vdW crystals, remains obscure. In this work, 2D ferromagnetic vdW electride, [ RE Cl] 2+ ·2e − ( RE = Y and La) is reported with perfectly isolated ferromagnetic 2D blocks encompassing quasi-atomic electron layers. The ferromagnetism of the vdW electride with Curie temperature of 100 K originates from the spin-polarized quasi-atomic electrons with a substantial moment up to ∼0.91 Bohr magneton, which behave as magnetic elements in paramagnetic lattice framework. Invariable ferromagnetism at the monolayer limit strongly supports the 2D ferromagnetism of quasi-atomic electrons. These findings expand the variety of 2D magnetic crystals, providing a promising platform to study the emergent magnetism of low-dimensional electron phases. Graphical abstract: Image 1 Highlights: First experimental demonstration of 2D vdW electride with IAEs confined at intralayer. The ferromagnetism originates from the spin-polarized quasi-atomic anionic electrons. 2D ferromagnetism at monolayer limit is verified, demonstrating critical role of IAEs for the ferromagnetism. The electron layer realizes an intrinsic 2D ferromagnetism of electron itself.